1994
DOI: 10.1080/09553009414550641
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Induction of Germline Mutation at a Hypervariable Mouse Minisatellite Locus

Abstract: Paternal 60Co gamma-irradiation was tested for the induction of germline mutation at the mouse hypervariable minisatellite locus, Ms6hm. Male C3H/HeN mice were exposed to 3 Gy 60Co gamma-ray and mated with C57BL/6N females. Matings were made at 1-7, 15-21 and 71-77 days post-treatment to test spermatozoa, spermatids and spermatogonia stages. Reciprocal crosses were also made with irradiated C57BL/6N males. Southern analysis was carried out on DNA from parents and F1 mice. The paternal mutation frequencies per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 25 publications
5
65
1
Order By: Relevance
“…Indeed, DNA ®ngerprint analysis of the o spring of 60 Co g-irradiated mice reveals minisatellite mutations in spermatogonia, with an estimated doubling dose of 0.5 Gy (Dubrova et al, 1993). Analysis of two single mouse minisatellite loci has also shown mutation radiosensitivity particularly in spermatocytes and spermatids (Sadamoto et al, 1994). However, the frequency of induced mutations appears to be in excess of the predicted frequency of strand breaks per locus, suggesting that minisatellite instability may not be initiated directly by radiation-induced damage, but instead be a result of some as yet unidenti®ed genomic alteration induced by ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, DNA ®ngerprint analysis of the o spring of 60 Co g-irradiated mice reveals minisatellite mutations in spermatogonia, with an estimated doubling dose of 0.5 Gy (Dubrova et al, 1993). Analysis of two single mouse minisatellite loci has also shown mutation radiosensitivity particularly in spermatocytes and spermatids (Sadamoto et al, 1994). However, the frequency of induced mutations appears to be in excess of the predicted frequency of strand breaks per locus, suggesting that minisatellite instability may not be initiated directly by radiation-induced damage, but instead be a result of some as yet unidenti®ed genomic alteration induced by ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms responsible for generation of these mutations are unknown. In mice, paternal irradiation results in a high frequency of new minisatellite repeat polymorphisms in a selected locus in the o spring (Sadamoto et al, 1994). Minisatellite instability was also reported with high frequency in the o spring of irradiated mice (Dubrova et al, 1993), and in xenografts of X-ray transformed mouse cells growing in vivo (Paquette and Little, 1994).…”
Section: Introductionmentioning
confidence: 96%
“…Dubrova and his group repeatedly demonstrated that the postmeiotic stage, as analysed by mating males at 3 weeks after irradiation, was insensitive to radiation induction of minisatellite mutations using three strains of mice including CBA/H (Dubrova et al, 1993(Dubrova et al, , 1998aBarber et al, 2000). In contrast, Niwa and his group reported that the postmeiotic irradiation of C3H/HeN males at 2 weeks prior to the mating is most effective in inducing minisatellite mutation (Sadamoto et al, 1994;Fan et al, 1995). Thus, the discrepancy may be due to the difference in the strain used.…”
Section: Minisatellite Mutation and Male Spermatogenesismentioning
confidence: 94%
“…This work was followed by a report of another group (Sadamoto et al, 1994). Owing to the highly frequent mutation and a small target size of the sequence, it was concluded that minisatellite mutation is untargeted and radiationinduced genomic instability is likely to be responsible (Sadamoto et al, 1994;Dubrova et al, 1998b). A series of works thereafter confirmed that the mouse minisatellite is sensitive to radiation induction of length change mutations, but several discrepancies are noted.…”
Section: Minisatellite Mutation and Male Spermatogenesismentioning
confidence: 99%
“…Although a radiation-induced increase in somatic mutation rate and risk of cancer was documented in a few studies, little is yet known about the impact of ionizing radiation on the mutability of human germ cells. Data obtained using model organisms have shown that ionizing radiation increases the rate of germ cell mutations (Neel & Lewis 1990;Dubrova et al 1993Dubrova et al , 1994Dubrova et al , 1998Sadamato et al 1994). In humans, however, it has not been convincingly demonstrated that exposure to low-dose radiation causes heritable changes in germ cells that lead to an increased rate of de novo mutations in the progeny.…”
Section: Introductionmentioning
confidence: 99%